An investigation into the impact of information behaviour on information failure: The Fukushima Daiichi nuclear power disaster. Issue 1 (February 2015) - Thatcher, Andrew; Vasconcelos, Ana C.; Ellis, David
Highlights Uses Fukushima Nuclear Power Disaster to illustrate role of information failure. Identifies impact of information behaviour on information failure. Reveals escalation of commitment to myth of nuclear safety. Explains how escalating commitment interacts with information behaviour. Shows information avoidance was a major factor in the Fukushima Disaster.